Soft solution growth of magnetite-maghemite nanocrystals in crosslinked chitosan templates and their superparamagnetic properties - Vaewbundit, Sukanda; Siriphannon, Punnama (My University, 2022)
Crosslinked chitosan/iron oxide nanocomposites (CC/IO) were synthesized at low temperatures using aqueous systems, i.e. hydrothermal and refluxing methods. The CC templates derived from various concentrations of tripolyphosphate crosslinker were used as host materials. The Fe2+ and Fe3+ ions with 1:2 molar ratio were adsorbed into the CC templates by the swelling, allowing to form CC/Fe2+Fe3+ precursors. The CC/IO nanocomposites were created by treating the precursors in NaOH solution using hydrothermal and refluxing methods. The CC/IO nanocomposites contained magnetite-maghemite nanocrystals with quadrilateral shape of 10 − 14 nm embedded in the CC templates. Superparamagnetism was obtained in the CC/IO nanocomposites, which had maximum magnetization (Mmax) values ranging from 8.6 to 15.2 emu/g and coercivity and magnetic remanence values close to zero. The cell viability of CC/IO nanocomposites ranged from 80 to 89%, demonstrating high safety for mammal. The CC/IO nanocomposites were considered to be potential superparamagenetic candidates for alternative medical applications.
Keywords: Chitosan; hydrothermal; maghemite; magnetite; nanocomposites; nanocrystals; refluxing; superparamagnetism